Faktor Yang Mempengaruhi Konsumen Memilih Kolam Renang Muslimah Al-Hikmah Sport Center di Surabaya - Anneke Ratnasari Hardianto; Ririn Tri Ratnasari (Universitas Airlangga, 2015)
The purpose of this study is to identify factors that influence consumers on choosing Al-Hikmah Sport Center Muslimah Swimming Pool in Surabaya. It related to increasing of people’s awareness to do physical activities, especially swimming.This study used quantitative research methods with exploratory factor analysis.Characteristics of the respondents in this study is Muslim consumers of Al-Hikmah Sport Center Muslimah Swimming Pool that have come at least twice in a last month. Sample amount on preliminary test by doing written interview are 20 respondents and the main test need 125 respondents. Sampling technique that used is non-probability sampling. Sampling was done using accidental sampling and purposive sampling.The results of the study showed that there are six factors that influence consumers on choosing Al-Hikmah Sport Center Muslimah Swimming Pool in Surabaya. The sixth factors are named by the factor of similarity motives, securities, location, facilities, water qualities, and the experiences.